Life-Cycle Monitoring of Long-Span PSC Box Girder Bridges through Distributed Sensor Network: Strategies, Methods, and Applications - Zheheng Chen; Tong Guo; Shengyou Yan (Shock and Vibration)
Structural health monitoring (SHM) has attracted much attention in recent years, which enables early warnings of structural failure, condition assessments, and rational maintenance/repair strategies. In the context of bridges, many long-span steel bridges in China have been installed with the SHM systems; however, the applications of the SHM in prestressed concrete (PSC) bridges are still rather limited. On the other hand, the PSC box girder bridges are extensively used in highway and railway systems and premature damage of these bridges is often reported, resulting in considerable maintenance and/or replacement costs. First, this paper presents a state-of-art review on the SHM of long-span PSC bridges. Monitoring strategies, methods, and previous applications for these bridges are summarized and discussed. In order to well capture the behavior of the bridge during its whole life and to maximize the use of sensors, a life-cycle monitoring strategy is proposed, in which the sensor layout is determined according to requirements for construction monitoring, completion test, and in-service monitoring. A case study is made on a three-span PSC box girder bridge in China. The system configuration, sensor layout, and data communications, and so forth, are presented. The up-to-date monitored structural responses are analyzed and compared with the design values.